EMBRACING NEW NORMAL: COPING WITH COURSE LEARNING OUTCOMES AMID COVID-19 PANDEMIC - Lina Septianasari; Irma Wahyuni (Premise: Journal of English Education and Applied Linguistics, 2021)
This paper aims to throw light on the students’ perception of emergency remote learning and their assessments in completing the Course Learning Outcomes (CLOs). The methods used in this study were statistical quantitative and descriptive qualitative methods. The data were collected by spreading questionnaires to the participants, having an unstructured interview, and taking the secondary data from the classroom teachers. LISREL software was used to analyze the quantitative data and descriptive interpretation was also done to analyze the qualitative data. The finding showed that most students had moderate to positive learning engagement, motivation, and self-efficacy in which affected their CLOs. The students who failed to pass the CLOs were those who faced more challenges in joining the virtual class. In short, students’ ability to cope with emergency remote learning has significant impacts on their CLOs’ assessments.